Implementation of Assessment for Islamic and Catholic Religious Values Development - Selvi, Issaura Dwi (Indonesian Journal of Early Childhood Education Studies, 2020)
Religious assessments in Indonesian Kindergartens must be based on the applicable curriculum. For schools based on certain religions, there is no difficulty in evaluating religion. But it is different with the National Kindergarten school that has children with different religious backgrounds. This is the reason the researchers conducted research on how to carry out religious assessments at the TK Yayasan Wanita Kereta Api (YWKA) Yogyakarta National Foundation. The purpose of this reseach are to describes implementation and process assessment for Islamic and Catholic religious values development in Yayasan Wanita Kereta Api’s National School. The type of this research is qualitative. The method used is participant observation. The results and discussion show that the implementation of assessments of the development of Islamic and Catholic values of children aged 4-6 years at YWKA Yogyakarta Kindergarten is the implementation of assessments of Islamic religious values using performance sheets by assessing religious education, creed, and morals seen from the process of evaluating reading Iqro '. The process of assessing Catholic religious values using anecdotal notes. The results of children's religious values are known to develop as expected (BSH). Therefore despite these different beliefs, the development of children's religious values is good and is in line with educational goals.